Different evolution of 3 infantile hemangiomas in the same subject. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Immediately after the discovery of the effectiveness of propranolol in the treatment of infantile hemangioma (2) physicians became aware of the differences compared to the old corticosteroid treatment: greater efficiency, lower and different side effects and increased incidence of rebound phenomenon (1). The latter does not occur immediately after discontinuation of the drug, but usually after weeks or months. When hemangiomas are more than one in the same subject their natural history and response to propranolol is not always the same; among the factors that make it different there is the site involved; the latter acts on the basis of extrinsic - temperature, humidity, light exposure - and intrinsic factors - resistance to the growth of the tissues surrounding the HE, movements due to the activity of muscle and joint structures, changes in blood pressure characteristic of the site affected.